2010
DOI: 10.1002/cssc.201000118
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐Film Composite Materials as a Dielectric Layer for Flexible Metal–Insulator–Metal Capacitors

Abstract: A new organic-organic nanoscale composite thin-film (NCTF) dielectric has been synthesized by solution deposition of 1-bromoadamantane and triblock copolymer (Pluronic P123, BASF, EO20-PO70-EO20), in which the precursor solution has been achieved with organic additives. We have used a sol-gel process to make a metal-insulator-metal capacitor (MIM) comprising a nanoscale (10 nm-thick) thin-film on a flexible polyimide (PI) substrate at room temperature. Scanning electron microscope and atomic force microscope r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The fabricated sensor showed sensitivity to a relative humidity of 0.38% (RH) and a linearity R 2 (0.996) in the range of 10-90 RH%. Tiwari et al [39] fabricated organic-organic nanoscale composite thin-film (NCTF) by using a sol-gel method where the precursor solution has been achieved with organic additives using solution deposition of 1-bromoadamantane and triblock copolymer (Pluronic P123, BASF, EO 20 -PO 70 -EO 20 ). The sol-gel process was used to make metalinsulator-metal capacitor (MIM) comprising of a nanoscale (10 nm-thick) thin-film on a flexible polyimide (PI) substrate at room temperature.…”
Section: Dobrzynska and Gijsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabricated sensor showed sensitivity to a relative humidity of 0.38% (RH) and a linearity R 2 (0.996) in the range of 10-90 RH%. Tiwari et al [39] fabricated organic-organic nanoscale composite thin-film (NCTF) by using a sol-gel method where the precursor solution has been achieved with organic additives using solution deposition of 1-bromoadamantane and triblock copolymer (Pluronic P123, BASF, EO 20 -PO 70 -EO 20 ). The sol-gel process was used to make metalinsulator-metal capacitor (MIM) comprising of a nanoscale (10 nm-thick) thin-film on a flexible polyimide (PI) substrate at room temperature.…”
Section: Dobrzynska and Gijsmentioning
confidence: 99%
“…Nanocomposites can provide high capacitance densities, ranging from 5 nf/inch 2 to 25 nF/inch, depending on composition, particle size, and film thickness as conductive joints for high frequency and high density interconnect applications [40].Organic-organic nanoscale composite thin-film (NCTF) dielectric by solution deposition with the sol-gel process used to make a metal-insulator-metal capacitor (MIM) [39].The low-cost flexible substrate is another research area and there are different applications for ultralow-cost RFID tags [45]. Flexible, high-κ BaTiO 3 @RGO/PI composites have promising potential applications for capacitors and electronic devices in the fields of microelectronics [62].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…However, above methods require ultrahigh vacuum condition and expensive tools. The solgel spin-coating method is a very efficient approach toward crack-free and smooth ceramic films in prior to thermal annealing limitation for plastic substrate [3,12]. In addition, such films can be fabricated at room temperature and normal pressure, obviating the need for high-vacuum systems [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research studies have found that high k material might lead to electrical degradation of the devices due to the undesired interaction between organic semiconductors (OSCs) and high k dielectric layer [10]. However, low k materials provide benefits of minimum Resistance-Capacitance delay (R-C), cross talk noise and power dissipation [11]. Currently, there have been an increasing demand of reducing the feature size of microelectronics but as device size is decreased Resistance-Capacitance delay increases which is a serious limitation to the scaling down dimension.…”
Section: Introductionmentioning
confidence: 99%